2019
DOI: 10.21303/2504-5695.2019.00857
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Honey Geographic Origin According to Its Elemental Composition by the Method of X-Ray Fluorescence

Abstract: The aim of the research was to determine features of the elemental composition of polyfloral honey from the Odessa region (Ukraine) by the method of x-ray fluorescence for using these features in the geographic marking of the region of honey origin. A choice of honey from the Odessa region is explained by its relatively good ecology, optimal maritime climate and enough motley grass resources for gathering nectar by bees. At the same time the Odessa region occupies the fourth place among regions – honey produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Furthermore, the mineral content of honey is related to other physicochemical parameters, such as color. In general, it is observed that light floral honey has lower ash content (0.2-0.3%) compared to darker honey (0.5-0.6%) [41][42][43].…”
Section: Physicochemical Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the mineral content of honey is related to other physicochemical parameters, such as color. In general, it is observed that light floral honey has lower ash content (0.2-0.3%) compared to darker honey (0.5-0.6%) [41][42][43].…”
Section: Physicochemical Analysismentioning
confidence: 96%
“…Furthermore, it has been shown that the trace element content in honey is related to its botanical origin and color. Floral honey generally has a lower mineral content compared to dark honey types such as honeydew, chestnut, and heather honey [41]. However, this determination is not only useful for assessing the botanical origin of honey but also its geographical origin.…”
Section: Electrical Conductivitymentioning
confidence: 99%